Ability of Select Probiotics to Reduce Enteric Campylobacter Colonization in Broiler Chickens - Shrestha, S.; Arsi, K.; Wagle, B.R.; Donoghue, A.M.; Donoghue , D.J. (International Journal of Poultry Science, 2017)
Background and Objective: Campylobacter is the leading cause of foodborne enteritis worldwide and is primarily caused by consumption/mishandling of contaminated poultry. Probiotic use in poultry has been an effective strategy in reducing many enteric pathogens, but has not demonstrated consistent reduction against Campylobacter. This study was conducted to screen probiotic isolates that could eliminate or reduce cecal Campylobacter counts in poultry. Materials and Methods: As Campylobacter resides and utilizes intestinal mucin for growth, isolates selected on the basis of mucin utilization might be a strategy to screen for probiotic candidates with efficacy against Campylobacter . In this study, bacterial isolates demonstrating increased growth rates in the presence of mucin in media, in vitro were selected for their ability to reduce Campylobacter colonization in 14 day old broiler chickens. In replicate trials, 90 days-of-hatch chicks were randomly divided into 9 treatment groups (n = 10 chicks/treatment) and treated individually with one of four bacterial isolates (Bacillus spp.) grown in media with or without mucin prior to inoculation or a Campylobacter control (Campylobacter , no isolate). In both the trials, all the birds except control were orally gavaged with individual isolates at day-of-hatch. On day 7, all the birds were orally challenged with a four strain mixture of C. jejuni and ceca were collected on day 14 for Campylobacter enumeration. Results: Results from these two trials demonstrated two individual isolates, one isolate incubated with mucin in the media and another isolate incubated without mucin prior to inoculation, consistently reduced cecal Campylobacter counts (1.5-4 log reduction) compared to controls. Conclusion: These results support the potential use of mucin to pre-select isolates for their ability to reduce enteric colonization of Campylobacter in broiler chickens.